Seleccion de hongos entomopatogenos para el control de Bemisia tabaci - Espinel, C.=700 1 Torres, L.; Gonzalez, V.; Cotes, A.M.
(Es, En)
Ilus., 14 ref.
Keywords: BEMISIA TABACI; ENSAYO BIOLOGICO; CONTROL BIOLOGICO; HONGOS ENTOMOPATOGENOS; BEAUVERIA BAáIANA; LECANICILLIUM LECANII; PAECILOMYCES; COSTA RICA; MOSCA BLANCA